If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4 + -3y) = 3y + 6 (4 * -3 + -3y * -3) = 3y + 6 (-12 + 9y) = 3y + 6 Reorder the terms: -12 + 9y = 6 + 3y Solving -12 + 9y = 6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -12 + 9y + -3y = 6 + 3y + -3y Combine like terms: 9y + -3y = 6y -12 + 6y = 6 + 3y + -3y Combine like terms: 3y + -3y = 0 -12 + 6y = 6 + 0 -12 + 6y = 6 Add '12' to each side of the equation. -12 + 12 + 6y = 6 + 12 Combine like terms: -12 + 12 = 0 0 + 6y = 6 + 12 6y = 6 + 12 Combine like terms: 6 + 12 = 18 6y = 18 Divide each side by '6'. y = 3 Simplifying y = 3
| 2(6x+8)-5=12x+11 | | (2+3)x(3+3)=x | | 0.51m+0.03=0.4m-0.74 | | -7(k-1)-5=-2(k-6) | | 26=6(5+-1a) | | 7x+15=3(2-y) | | 5z+15=4z+5 | | y^2+4=400 | | [x/3-6]=(2x+4)(-1/2) | | 8y-3=-3 | | 20=3-(z+10) | | 3x+30=x | | -3(t-2)+9t=8t-6 | | -31-a=-(1-4a) | | 3x+30= | | -3(5y-9)-y=-3(y-3) | | 4(3+3x)-1=47 | | 5-2y=11-8y+6y | | .66m-.6m=4 | | 3x-6+6x=-15 | | 6(-2x-2)=-72 | | 1+3n-5n-4=1-4n | | 93-(7x+12)=7(x+3)+x | | .5xh+.33x(h-6)=.83xh+2 | | -5(t-5)+8t=6t-1 | | 5x-5=-3x-9 | | (x/3-6)=(2x+4)(-1/2) | | 3(y-5)-5y=5y+9 | | 8-4z=16 | | 7x-8=7x-8 | | 8x-3y=6-4x | | 13=.167x+2y |